Emotional tranquility and its relationship to cognitive and practical motivation among first-year students at the College of Physical Education and Sports Sciences - Hamid, Asst.L. Sarah Akram; Abdul-Razzaq, Prof. Dr. Firas Abdul-Moneim (Sulaimani Journal for Humanities, 2026)
The current study aims to explore the varying degrees of emotional well-being experienced by individuals. A lack of emotional well-being can hinder a student's ability to cope with the challenges and difficulties of university life. Therefore, an individual's sense of self-worth, tranquility, and self-confidence—which constitutes emotional well-being—is a crucial human need, essential for everyone's life and considered one of the most prominent needs driving the continuation of human behavior. Students who experience emotional well-being tend to have positive feelings about themselves. The research aims to identify emotional well-being and cognitive and practical motivation among first-year students in the College of Physical Education and Sports Sciences, and to determine the relationship between emotional well-being and cognitive and practical motivation among these students. The research problem concerns the extent to which the educational aspect is influenced by the psychological aspect, and its ability to impact cognitive and practical performance, success, and creativity. Any imbalance in this aspect hinders academic performance and affects students' emotional well-being. The researchers employed a descriptive survey methodology with correlational relationships, as it is the most suitable approach for the nature of the problem and for achieving its objectives. The research objectives included a population of (240) first-year students (male and female) at the College of Physical Education and Sports Sciences, University of Diyala, for the academic year (2024-2025). The research sample was selected from this population of (150) students, representing 62.5% of the total population, divided into (20) pilot samples and (100) students for the main experiment.
Keywords: For emotional reassurance; cognitive and practical motivation